2017
DOI: 10.3389/fpsyg.2017.00732
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Authoritarian Leadership and Employees’ Deviant Workplace Behaviors: The Mediating Effects of Psychological Contract Violation and Organizational Cynicism

Abstract: This study investigated the relationship between authoritarian leadership and employees’ deviant workplace behaviors (DWB), as well as the mediating effects of psychological contract violation and organizational cynicism. A cross-sectional survey was conducted among 391 manufacturing workers in a northern city of China. Structural equation modeling was performed to test the theory-driven models. The results showed that the relationship between authoritarian leadership and employees’ DWB was mediated by organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 67 publications
5
101
0
2
Order By: Relevance
“…First of all, the results show that an authoritarian leadership style is negatively associated with empowerment. For this purpose, the presence of an authoritarian regime of leadership is undesirable and should be avoided and reduced by careful selection [88]. Moreover, courses and training programs on the improvement of interpersonal relationship skills of leaders are highly recommended [12], as they could help them to be more evaluative and understanding towards subordinates.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…First of all, the results show that an authoritarian leadership style is negatively associated with empowerment. For this purpose, the presence of an authoritarian regime of leadership is undesirable and should be avoided and reduced by careful selection [88]. Moreover, courses and training programs on the improvement of interpersonal relationship skills of leaders are highly recommended [12], as they could help them to be more evaluative and understanding towards subordinates.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…In the present study, taking Hypothesis 1–3 into consideration, when employees perceive PCB they will judge they were treated unfavorably by the organization, which causes them to believe that the organization lacks integrity. In such cases, employees will show organizational cynicism and then engage in CWB (Jiang et al, 2017a). In addition, Steele’s (2014) study confirmed that organizational cynicism mediated the relationship between PCB and workplace behaviors.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Conversely, where there is low-quality LMX, subordinates are not obligated to increase effort to benefit supervisors and organizations (Gouldner 1960). In addition, according to the principle of negative reciprocity, which states that those who receive unfavorable treatment will respond with unfavorable behaviors (Gouldner 1960), because subordinates of authoritarian leaders receive unfavorable treatment, such as being strictly controlled and being compelled to obey unconditionally, these subordinates may respond with undesirable behaviors, such as withholding their effort and engaging in more deviant workplace behavior (Jiang et al 2017).…”
Section: Authoritarian Leadership and Lmxmentioning
confidence: 99%
“…A substantial body of empirical research has also explored the influence of authoritarian leadership on followers' work-related behavior and outcomes. Authoritarian leadership is negatively related to employee voice (Chan 2014;Li and Sun 2015), organizational citizenship behavior (Chan et al 2013), employee creativity (Guo et al 2018), and employee performance (Chan et al 2013;Schaubroeck et al 2017;Shen et al 2019;Wu et al 2012), and such leadership is positively associated with employee deviant workplace behavior (Jiang et al 2017). In particular, studies concerning authoritarian leadership and employee performance have suggested that authoritarian leadership is negatively related to employee performance because subordinates of authoritarian leaders are likely to have low levels of the following: trust-in-supervisor, organization-based self-esteem, perceived insider status, relational identification, and thus, little motivation to improve performance (Chan et al 2013;Schaubroeck et al 2017;Shen et al 2019;Wu et al 2012).…”
Section: Introductionmentioning
confidence: 99%